ANALYSIS OF THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH (OSH) ON ROAD ASPHALT WORKERS IN PONTIANAK CITY - Hasan, Ishak; Elvira, Elvira; Priadi, Eka; Nurhayati, Nurhayati; Widodo, Slamet (Fakultas Teknik Universitas Tanjungpura, 2023)
The implementation of infrastructure activities, whether in the form of building construction or road construction, always requires and involves a large number of workers, construction activity organizers, especially service providers or contractors who have a workforce of various levels directly related to the field, especially workers in the area are very vulnerable to occupational safety and Health, especially in road paving work in cities, where asphalted roads are roads with high and dense vehicle traffic. For this reason, the authors conducted an Analysis of the Effect of Occupational Safety and Health on Road Paving Workers in Pontianak City.All data must first be tested for data validity and reliability using the statistical program SPSS Version 26 to find out the analysis results. The data processing method uses quantitative methods. Then the Author will carry out a regression analysis so that it can be seen to what extent the influence of hazard and risk identification safety at work on occupational risk control, occupational safety, and health programs on road paving work in the city of Pontianak, as well as to find out the dominant factors that determine the value of occupational risk control.